Forest Resource Use Patterns in a Protected Forest Reserve in Western Zimbabwe-the Case of Fuller Protected Forest - Mudekwe, J. (International Journal of Bio-resource and Stress Management, 2017)
Communal households in Zimbabwe are no different to other areas of the developing world when it comes to harvesting natural forest resources. A range of forest resources is harvested from protected forests and woodlands for direct home consumption and for sale. In Zimbabwe only a few studies have attempted to describe and characterise the dynamics of forest product use by communities living adjacent to protected forests. This study was conducted in the Baikiaea plurijuga forests in Fuller Forest, western Zimbabwe, protected since 1943. The study explored the characteristics and dynamics of forest resource use by communities surrounding this protected forest. Results indicated that all households, rich and poor, were harvesting at least some forest resources from the protected forest. The most frequently harvested resources being firewood, wood for curios, thatch grass, wild fruits, timber for construction and fencing and those who owned livestock used the forest for livestock grazing. The extraction and use of 23 different products was recorded across five villages. The top five harvested forest products in terms of the mean proportion of households using them were fuelwood, building poles, thatch grass, wild fruits and broom grass. Forest products were harvested both for own consumption and for sale.